Perceived barriers to healthy eating among overweight and obese women: a qualitative study - D. Herath; A. Kasturirathne (College of Community Physicians of Sri Lanka, 2023)
Introduction: Being overweight/obese is a global epidemic and one of the leading causes of cardiovascular diseases (CVD). Knowing the barriers to a healthy lifestyle in target populations is necessary to further reduce the burden of overweight/obesity, which can ultimately reduce the mortality and morbidity following non-communicable diseases (NCDs). Objectives: To describe the perceived barriers to healthy eating among 35-44 aged overweight/obese women. Methods: A qualitative study was conducted in Panadura Medical Officer of Health (MOH) Area in the district of Kalutara, Sri Lanka. The data were collected using semi-structured in-depth interviews conducted among 18 overweight/obese women. Content analysis of the qualitative data was conducted manually. Coding was decided following a discussion with two independent experts in the field of public health. Using the inductive approach to data analysis ensured that the interpretations and codes of the study were generated from the actual data. Results: The study identified three main themes which included personal, social, cultural, and environmental barriers as key factors for perceived healthy eating. Under the personal factors, inadequate knowledge, time limitation, lack of motivation, and inadequate cooking skills were identified as subthemes. Social and cultural barriers included two subthemes: immediate family influence and social norms, while environmental barriers included two subthemes: lack of access to healthy options and high cost of healthy options. Conclusions & Recommendations: Study findings provide important insights into challenges and perceived barriers to healthy eating, which highlight the need for further research based on barrier profiles to design and develop more attractive and realistic community prevention programs for healthy eating.